Ivy + Bean - Barrows, Annie; Blackall, Sophie (San Francisco : Chronicle Books, 2006)
When seven-year-old Bean plays a mean trick on her sister, she finds unexpected support for her antics from Ivy, the new neighbor, who is less boring than Bean first suspected.
Wilson's Children, October 2010.
Notable/Best Books (A.L.A.), January 2007.
School Library Journal, July 2006.
Book Links (A.L.A.), September 2006.
Booklist starred, April 2006.
Pub Weekly, May 2006.
Keywords: Friendship -- Juvenile fiction; Neighbors -- Juvenile fiction; Friendship -- Fiction; Neighbors -- Fiction